Creation and evolution in primitive cosmogonies, and other pieces - Frazer, James George, 1854-1941. (London : MacMillan and Co. Limited, 1935)
p.7; Legend of Pund-jel, the creator (Melbourne); p.17; Notes on Cassowary totemic clan (Mabuiag); p.29-34; 3 Dieri origin legends; Arunta embryo legend, lists clans known to have originated from embryos, all circumcised with fire-stick except Plum Tree men; p.55-69; Notes on Baldwin Spencer and his work in Central Australia.
Keywords: Frazer, James George, -- 1854-1941.; Condorcet, Jean-Antoine-Nicolas de Caritat, -- marquis de, -- 1743-1794.; Spencer, Baldwin, -- Sir, -- 1860-1929.; Creation; Religion - Totemism; Initiation - Circumcision; Stories and motifs - Creation / Cosmology; Torres Strait Islanders (Qld TSI SC54, SC55); Environment - Land management - Fire; Animals - Birds - Cassowaries; Diyari / Dieri people (L17) (SA SH54-01); Technology - Wood - Fire sticks; Arrernte / Aranda people (C8) (NT SG53-02); Human biology - Physical anthropology - Human evolution; Mabuiag / Jervis Island (Qld TSI SC54-07); Melbourne (Vic SJ55-05); Northern Territory - Central NT; Queensland (Qld); North East South Australia (NE SA SG54, SH54); South Australia - Central Australia (SA SG52, SG53)